A cross-country study of skills and unemployment flows - Damir Stijepic (Journal for Labour Market Research, 2021)
Using an international survey that directly assesses the cognitive skills of the adult population, I study the relation between skills and unemployment flows across 37 countries. Depending on the specifically assessed domain, I document that skills have an unconditional correlation with the log-risk-ratio of exiting to entering unemployment of 0.65-0.68 across the advanced and skill-abundant countries in the sample. The relation is remarkably robust and it is unlikely to be due to reverse causality. I do not find evidence that this positive relation extends to the seven relatively less advanced and less skill-abundant countries in the sample: Peru, Ecuador, Indonesia, Mexico, Chile, Turkey and Kazakhstan.
Keywords: J20; J24; J60; J64; I20; 330; Gross worker flows; Unemployment; Skills; Education; Human capital; International comparisons; Survey of Adult Skills; PIAAC